Sistem Predictive Maintenance Bearing Pada Mesin Super Mixer Granula Dengan Menggunakan Sensor Acceelerometer MPU-6050 - Oktavianus Ardhian Nugroho; Catherine Angel Tandiawan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
PT Hexpharm Jaya Laboratories is one of the companies that is part of Kalbe Company which is specially engaged in the development, production, processing, and marketing of drugs. The process of processing medicinal raw materials at PT Hexpharm Jaya Laboratories uses several machines, one of which is the SMG (Super Mixer Granula) machine. This machine is used to mix medicinal raw materials and is the initial processing process before it becomes a granule. The problem that often arises in this machine is the problem of replacing bearings. Bearings attached to the shaft section connecting the gearbox with granules are often subject to damage that causes production stops/breakdowns. This unplanned maintenance process has previously been tried to be overcome by calculating the life of the bearing and alignment shaft connecting to reduce vibrations, but the bearing still suffers untimely damage. In this paper, a system was created to predict when the bearings need to be replaced by recording vibration data that occurs. The purpose of this study is to obtain a system that prevents unplanned maintenance so that it does not interfere with the production process Using the MPU-6050 sensor the vibrations on the bearings are measured and recorded during the machine's 12-hour operation. The results are obtained by a predictive maintenance system that can prevent breakdowns that result in the cessation of the production process. The system is created by recording vibrations that occur when the machine is working and is used as a way to predict the lifetime of the bearing. The system successfully measures the vibration value of the bearing and can be displayed, helping the maintenance technician estimate the exact time for bearing replacement in the SMG machine.